Dark matter distributions in the central region of late type NGC3256 and NGC4321 Galaxies / Israa Abdulqasim Mohammed Ali - Israa Abdulqasim , Mohammed Ali (2018)
The distribution of the unseen matter (also known as the dark matter) in the galaxies defines their formation, evolution and dynamics. The mass distribution of a few galaxies is studied using the CO observations of Atacama Large Millimeter/sub-millimeter Array (ALMA) and the near Infrared (near-IR) data of the Two Micron All Sky Survey (2MASS). The dark matter has been investigated for the late type galaxies and active galaxies. Results indicate a vast amount of invisible dynamical mass ( 109M_) in the central region of the galaxy, which cannot be explained by the molecular and stellar masses within this region. The expected mass of the supermassive black hole (SMBH) in the galaxy is much smaller than its dynamical mass and it is inferred from the SMBH-bulge relation and other suitable ways. The mass of the SMBH cannot significantly contribute to the dynamical mass. The invisible mass is likely caused by dark matter, which might have a cuspy dark matter profile. In addition to the dark matter investigation in this thesis, the alternative of the dark matter (i.e.Modified Newtonian Dynamics (MOND)) is also looked into. The latter could not explain the dark matter because of the relative strong acceleration in the central region of galaxies. This study might also thus pose a challenge to the MOND models.